"Not for Everyone": Transformations of Italian Calcio in the Digital Age. (2nd January 2021) - Beretta, Francesca
Abstract : The age of new media has changed soccer and soccer fans. In the past, clubs primarily focused on promoting the value of their brands through merchandise and the image of top players, while fans were mainly spectators. Digital transformations have allowed clubs to encourage fans' participation and engagement in new ways. In Italy, the Chinese-owned Inter Milan has become a leader in digital innovation launching Inter Media House, a project that creates and shares content across various platforms, allowing fans to experience the brand in the first person.